Augmented Reality Sebagai Media Pembelajaran di Rumah yang Efektif tetapi Menarik - Fajriansyah, Muhammad Azra; Widodo, Suprih (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
Education is a basic need that every people must obtain for every human being. The goal is as a medium to develop potential and educate humans so that they are ready to face the life to come. Technology in its development moves very fast. Today's technology can also be used as a tool that can help students in learning. Augmented Reality or commonly abbreviated as AR is a technology that combines virtual objects with natural objects. AR can produce visual forms from virtual objects such as objects or animals that can be seen in 3D so that the thing looks real. AR can be an exciting learning medium because it connects, provides information, and conveys messages to create a more effective and efficient learning process. The method used in this research is a Systematic Literature Review. Its purpose is to identify, review, evaluate and interpret available research on related topics. Based on the study results, it can be concluded that Augmented Reality can improve students' problem-solving abilities. In addition, Augmented Reality is also based on research getting a positive response in terms of effectiveness.